Serum Uric Acid, Alzheimer-Related Brain Changes, and Cognitive Impairment - Kim, Jee Wook; Byun, Min Soo; Yi, Dahyun; Lee, Jun Ho; Jeon, So Yeon; Ko, Kang; Jung, Gijung; Lee, Han Na; Lee, Jun-Young; Sohn, Chul-Ho; Lee, Yun-Sang; Shin, Seong A; et al. (Frontiers in Aging Neuroscience, 2020)
Background Despite known associations of lower serum uric acid (UA) with Alzheimer’s disease (AD) dementia or AD-related cognitive impairment, little is known regarding the underlying patho-mechanisms. We aimed to examine the relationships of serum UA with in vivo AD pathologies including cerebral beta-amyloid (Aβ) and tau deposition, AD-signature region cerebral glucose metabolism (AD-CM), and white matter hyperintensities (WMH). We also investigated the association between serum UA and cognitive performance, and then assessed whether such an association is mediated by the brain pathologies. Methods A total of 430 non-demented older adults underwent comprehensive clinical assessments, measurement of serum UA level, and multimodal brain imaging, including Pittsburgh compound B-positron emission tomography (PET), AV-1451 PET, fluorodeoxyglucose (FDG)-PET, and magnetic resonance imaging scans. Mini-Mental State Examination (MMSE) and word list recall (WLR) test scores were used to measure cognitive performance. Results Serum UA level was significantly associated with AD-CM, but not with Aβ deposition, tau deposition, or WMH volume. Serum UA levels also had significant association with WLR and marginal association with MMSE; such associations disappeared when AD-CM was controlled as a covariate, indicating that AD-CM has a mediating effect. Conclusion The findings of the present study indicate that there is an association of low serum UA with AD-related cerebral hypometabolism, and whether this represents a causal relationship remains to be determined.